Plant traits related to nitrogen uptake influence plant‐microbe competition. Issue 8 (1st August 2015) - Moreau, Delphine; Pivato, Barbara; Bru, David; Busset, Hugues; Deau, Florence; Faivre, Céline; Matejicek, Annick; Strbik, Florence; Philippot, Laurent; Mougel, Christophe
Abstract : Plant species are important drivers of soil microbial communities. However, how plant functional traits are shaping these communities has received less attention though linking plant and microbial traits is crucial for better understanding plant‐microbe interactions. Our objective was to determine how plant–microbe interactions were affected by plant traits. Specifically we analyzed how interactions between plant species and microbes involved in nitrogen cycling were affected by plant traits related to nitrogen nutrition in interaction with soil nitrogen availability. Eleven plant species, selected along an oligotrophic–nitrophilic gradient, were grown individually in a nitrogen‐poor soil with two levels of nitrate availability. Plant traits for both carbon and nitrogen nutrition were measured and the genetic structure and abundance of rhizosphere microbial communities, in particular the ammonia oxidizer and nitrate reducer guilds, were analyzed. The structure of the bacterial community in the rhizosphere differed significantly between plant species and these differences depended on nitrogen availability. The results suggest that the rate of nitrogen uptake per unit of root biomass and per day is a key plant trait, explaining why the effect of nitrogen availability on the structure of the bacterial community depends on the plant species. We also showed that the abundance of nitrate reducing bacteria always decreased with increasing nitrogen uptake per unit of root biomass per day, indicating that there was competition for nitrate between plants and nitrate reducing bacteria. This study demonstrates that nitrate‐reducing microorganisms may be adversely affected by plants with a high nitrogen uptake rate. Our work puts forward the role of traits related to nitrogen in plant–microbe interactions, whereas carbon is commonly considered as the main driver. It also suggests that plant traits related to ecophysiological processes, such as nitrogen uptake rates, are more relevant for understanding plant–microbe interactions than composite traits, such as nitrophily, which are related to a number of ecophysiological processes.